UPAYA PENCEGAHAN DAN PENGENDALIAN DIABETES MELITUS BERDASARKAN DATA POSBINDU PTM DI PUSKESMAS TAHTUL YAMAN - Rini, Willia Novita Eka; Guspianto, Guspianto; Maharani, Andini Dwi (Prodi Ilmu Kesehatan Masyarakat, FKIK Universitas Jambi, 2023)
Diabetes Mellitus is a metabolic disease characterized by high blood glucose levels (hyperglycemia) as a result of a deficiency of insulin secretion, impaired insulin activity or both. This Community Service (PKM) aims to carry out efforts to prevent and control Diabetes Mellitus in the Tahtul Yaman health center area. The activities carried out were counseling and outreach with the theme